Thermally Triggered Isomerization in a Naphthalene‐Based Acylhydrazone with Solid‐State Optical Nonlinearity Response. Issue 45 (5th November 2020) - Huang, Miaoling; Qiu, Rongxing; Pan, Zhonghua; Tian, Dan; Tao, Yunwen; Lin, Jinqing; Luo, Geng‐Geng
Abstract : Under the assistance of the state‐of‐the‐art meta‐dynamics simulations, in this contribution, we report a push‐pull‐type acylhydrazone 4 ( Z ) ([ Z )‐2‐(naphthalen‐2‐yloxy)‐ N' ‐(pyridine‐2‐ylmethylene)acetohydrazide] connecting an electron‐donating naphthalene ether group with an accepting pyridyl unit, which could be thermally converted to its configurational isomer 4 ( E ) ([ E )‐2‐(naphthalen‐2‐yloxy)‐ N' ‐(pyridine‐2‐ylmethylene)acetohydrazide]. The thermally triggered Z ‐to‐ E configurational isomerization not only involves up to five chemical bonds undergoing 180° rotation in the backbone of acylhydrazone, but changes the crystal packing symmetry from a centrosymmetric space group to a non‐centrosymmetric one. Most impressively, the acentric crystal arrangement of 4 ( E ) exhibits a second‐harmonic generation (SHG) active response, about 2.5 times than that of KH2 PO4 (KDP) standard. Abstract : The thermal Z → E isomerization of a push‐pull type naphthalene‐based acylhydrazone has been investigated through a joint meta‐dynamics simulations and experiments. The configurational isomerization also changes the crystal packing symmetry from a centrosymmetric space group to acentric one with a concomitant second‐order NLO response.